Sistem Informasi Kalkulator Kesehatan dan Kebugaran Tubuh Berbasis Web - Rizky Wahyudi; John Bush Henrydunan; Muhammad Alfin; Debi Yandra Niska (LPPM STT Terpadu Nurul Fikri, 2025)
Health and fitness play a crucial role in improving the quality of life. This study aims to develop a web-based health calculator system capable of automatically, in real time, calculating health indicators such as ideal body weight, Body Mass Index (BMI), basic and daily calorie needs, and body fat levels. This system was built using the Waterfall method with HTML, CSS, PHP, and JavaScript technologies. To assess accuracy, testing was conducted on five user datasets by comparing the system's calculations with manual calculations using standard formulas. The difference between the two was calculated as the average relative deviation for each indicator: 0.13% (BMI), 0.84% (ideal body weight), 0.27% (basic calories), 0.27% (daily calories), and 0.73% (body fat levels). Since all deviations were <1%, the system's overall accuracy was estimated to exceed 99%. The test results can be further visualized graphically to clarify the comparison of values. The system also demonstrated ease of use and responsive performance. In conclusion, this system can be used as an accurate and practical educational tool to support self-monitoring of health.